2012
DOI: 10.1002/aic.13879
|View full text |Cite
|
Sign up to set email alerts
|

Production of argon free oxygen by adsorptive air separation on Ag‐ETS‐10

Abstract: in Wiley Online Library (wileyonlinelibrary.com).The purification of different components of air, such as oxygen, nitrogen, and argon, is an important industrial process. Pressure swing adsorption (PSA) is surpassing the traditional cryogenic distillation for many air separation applications, because of its lower energy consumption. Unfortunately, the oxygen product purity in an industrial PSA process is typically limited to 95% due to the presence of argon which always shows the same adsorption equilibrium pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
29
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 15 publications
1
29
0
Order By: Relevance
“…The ability of cation exchange in ETS-10 can be exploited, for instance, to design appropriate adsorbents for temperature/pressure swing adsorption (TSA/PSA) techniques. [9][10][11][12][13][14] In fact, ETS-10 has been suggested as an adsorbent for gas separation processes by several authors. 9,10,12,15,16 For instance, Al-Baghli et al 9 and Anson et al 12 reported that CH4 and hydrocarbons can be captured employing the adsorptive separation technique, while Kuznicki et al 4,17 evidenced the good capacities of ETS-10 to separate N2 from landfill gas and air.…”
Section: Introductionmentioning
confidence: 99%
“…The ability of cation exchange in ETS-10 can be exploited, for instance, to design appropriate adsorbents for temperature/pressure swing adsorption (TSA/PSA) techniques. [9][10][11][12][13][14] In fact, ETS-10 has been suggested as an adsorbent for gas separation processes by several authors. 9,10,12,15,16 For instance, Al-Baghli et al 9 and Anson et al 12 reported that CH4 and hydrocarbons can be captured employing the adsorptive separation technique, while Kuznicki et al 4,17 evidenced the good capacities of ETS-10 to separate N2 from landfill gas and air.…”
Section: Introductionmentioning
confidence: 99%
“…The potential for PSA separation of Ar/O2 mixtures of Ag-mordenite was immediately recognised 23 . In the next two decades, several articles and patents followed, describing adsorbents with greater selectivities and capacities, as well as more efficient O2-generating PSA processes 20,22,24,27,[29][30][31][32] .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, there is an urgent need for alternative technologies and novel materials for energy‐ and cost‐efficient oxygen separation from air. Zeolite molecular sieves have been used for O 2 adsorption and separation, but still fall short compared to recently reported solid state adsorbents based on high surface area, crystalline metal–organic frameworks (MOFs) . In this regard, selective adsorption of O 2 from N 2 using M 2+ based MOFs—M 3 (btc) 2 (M = Cr, Fe; btc 3 = 1,3,5‐benzenetricarboxylate) and MOF‐74 Fe—are shown to exhibit steep O 2 ‐adsorption isotherms at room temperature (RT) .…”
mentioning
confidence: 99%